Defining skill variables between U16 national team and non-national team ice hockey players - Haapea, I. (2011)
The purpose of the research is to determine does sport specific technical skill tests separate U16 national team players from those who are not selected to U16 national team. When the research started, was assumed three things: 1. The U16 male ice hockey national team players have better results in sport specific technical skill tests than those who are not selected in the U16 national team, 2. Height or weight of the player doesn`t affect to the results of the sport specific technical skill tests, and 3. Date of birth doesn`t affect to the selection of national team. Investigated subjects (N=230) constituted of 1995 born male ice hockey players. One group (N1=43) is U16 national team players and second group (N2= 187) is rest of 1995 born male ice hockey players who belonged to the C1- juniors SM- league teams. There were 13 teams that were tested, plus the U16 national team. Finnish Ice hockey Association decided these 13 teams. These 13 teams were tested in their own operating environment, during September and October of 2010. U16 national team players were tested in Sport Institute of Finland in Vierumäki, during national team camp in October 2010. The material of this thesis is constructed from broader research. This broader research is funded by Ministry of Education and it includes test results of football and basketball as well as ice hockey. The research includes sport specific technical skill tests, anthropometrical test, physical tests, and questionnaires related to players` training background, self-evaluation and coach assessment. Only the results of height, weight, date of birth, and sport specific technical skill tests of ice hockey are analyzed in this thesis.